Resilience in vulnerable university groups: An analysis of social work intervention strategies from the perspective of social inclusion - D. J. Mendoza Velazco; L. M. Alava Barreiro; T. K. Moreira Chica; E. M. Alcivar Medranda; S. A. Romero Chávez (Образование и наука)
Introduction. Resilience refers to the ability of individuals, groups or communities to adapt and recover in the face of adverse or stressful situations, such as violence, poverty, natural disasters or disease.                Aim. The present research aims to analyse the impact of social work intervention in strengthening resilience in vulnerable groups served by the Faculty of Humanistic and Social Sciences of the Technical University of Manabí during the 2023-A academic period, to identify the pedagogical intervention of social work in vulnerable groups, and to evaluate the effectiveness of the intervention strategies implemented by social work professionals.                Methodology and research methods. The quantitative paradigm was applied. The design corresponds to a non-experimental study. The population was 259 students of Social Work. The sample consisted of 70 students belonging to vulnerable groups. A questionnaire with 15 items was applied. Multiple regression analysis and ANOVA analysis were carried out.                Results. Among the results, the pedagogical intervention strategies applied by the social work professionals were effective. There is a positive impact on strengthening resilience in vulnerable groups, as well as on socio-economic and cultural factors. Social work pedagogical intervention strategies as well as socio-economic and cultural factors are important in strengthening resilience in vulnerable groups. Scientific novelty.                The scientific novelty of this study is that building resilience through inclusion stands out as a pedagogical component in social work and as a pillar that strengthens social work.                Practical significance. It is important to take socio-economic and cultural factors into account when designing and implementing these pedagogical strategies, as they can influence their effectiveness. It is also important to continue research on the factors that influence the development of resilience in vulnerable groups in order to design and implement more effective and sustainable educational intervention strategies.